Assessing agricultural eco-efficiency in Italian Regions. (September 2020) - Coluccia, Benedetta; Valente, Donatella; Fusco, Giulio; De Leo, Federica; Porrini, Donatella
Graphical abstract: Highlights: The eco-efficiency is an agricultural sustainability index for policy makers. Italian regions reach different levels in European Common Agricultural Policy (CAP) Northern Italian Regions show a strong productivity orientation of their farms. Southern Italian farms are more oriented towards sustainability and eco-efficiency. The Italian agricultural sector seems getting the CAP's sustainability goals. Abstract: Agriculture plays a key role in providing a wide range of ecosystem services, such as food, feed, fiber and biofuel, thus taking part in the economic development of countries. On the other hand, this sector also gives rise to negative externalities. The eco-efficiency has been considered as a meaningful index for assessing how efficient economic activities are in terms of resource-use and environmental pressures: measuring eco-efficiency provides policy makers with important information for developing policies focused on sustainable management and efficient use of natural resources in the agricultural sector. In this context, sustainable development is now one of the most important objectives of the European Union Common Agricultural Policy (CAP) that has a key role in facing the challenges of the new paradigm of sustainability of agriculture. In this direction, the aim of this paper is to evaluate the eco-efficiency of the Italian agricultural sector, as an index useful for emphasizing the differences among some national geographical areas. This paper tries to fill the lack of scientific studies on agricultural eco-efficiency in Italy, despite the strategic role played by Italy in Europe. For this purpose, the Data Envelopment Analysis (DEA) methodology was used, focusing on the integration between agricultural productivity and resource conservation, in order to develop a support tool for policy makers and managers. The analysis had shown a better orientation in saving resources for the Southern Regions and a greater orientation in productivity for the Northern Regions. Overall, Italy seems to have a good capacity for sustainable management of agricultural resources although there is still space for improvement. In this regard, the measurement of eco-efficiency provides a useful index for policy makers to achieve better performances in terms of agricultural sustainability. This means that CAP subsidies should be granted in exchange for specific environmental externalities provided by farmers as a result of more ecologically friendly management with a land use planning avoiding the depleting of Ecosystem Services rich areas, allowing for the achievement of a balance between economic growth and ecosystem protection. Although the paper has expanded the literature on agricultural eco-efficiency, this work has some limitations that could serve as a reference for future studies that can include other ecological variables such as the provision of some ecosystem services that can be enhanced or impacted by agricultural development. Finally, the challenge to realize sustainable agriculture can represent a long-term guarantee of food security as well as societal well-being.